Advances in the application of PD-1/PD-L1 immunotherapy for prostate cancer: a review - Hu, Guangqiang; Li, Zeng; Chen, Yongji; Liao, Hong; Zhou, Shukui (Frontiers in Immunology, 2025)
Prostate cancer (PCa), the most prevalent malignancy among male genitourinary cancers, is distinguished by its immunologically ”cold” phenotype with persistently high incidence and mortality. Radical prostatectomy and radiotherapy represent the current standard of care for localized prostate cancer. However, recurrence or progression occurs frequently, and advanced or metastatic disease is common at initial presentation. Recent progress in cancer immunotherapy reveals that modulation of immune responses represents an effective strategy for enhancing antitumor activity. Programmed Cell Death Protein 1 and Programmed Cell Death Ligand 1 (PD-1/PD-L1) inhibitors, which restore T-cell function and remodel the tumor immune microenvironment, have achieved clinical success in melanoma, lymphoma and non-small-cell lung cancer. Although their efficacy as monotherapy in PCa remains limited and optimal patient selection criteria are lacking, emerging evidence suggests that combination immunotherapy regimens may offer clinically significant benefits. This review critically evaluates current clinical trial outcomes involving PD-1/PD-L1 inhibitors for prostate cancer and outlines priority directions for future investigation.